PENGARUH EDUKASI TENTANG MENARCHE TERHADAP TINGKAT KECEMASAN DAN KESIAPAN MENGHADAPI MENARCHE PADA SISWI KELAS VI DI KABUPATEN SUKABUMI (Al-Insyirah Midwifery: Jurnal Ilmu Kebidanan (Journal of Midwifery Sciences), 2025)
Indonesia in 2018 saw 49.1% of adolescents aged 10-19 years experiencing anxiety about puberty including menstrual problems. Anxiety that is not addressed immediately causes various health problems that can interfere with activities. The purpose of the study was to determine the effect of education about menarche on anxiety levels and readiness to face menarche in grade VI female students in Sukabumi Regency. The research design used a quasi experiment pretest-posttest control group design. The study population was grade VI female students who had not menstruated with the number of samples in MI MWB 48, MI Muhammadiyah Cipetir 20, SDN Kadudampit 25. Data analysis used Wilcoxon and mann whitney. The Wilcoxon test found that there was an effect of education through video media, leaflets and lectures on anxiety levels and readiness to face menarche. Mann Whitney test anxiety level p-value 0.000 and readiness to face menarche p-value 0.702 means there is a difference in the effect of video media education with lecture media on anxiety levels and no difference in readiness to face menarche. Anxiety level p-value 0.046 and readiness to face menarche p-value 0.491 means that there is a difference in the effect of leaflet media education with lecture media on anxiety levels and there is no difference in readiness to face menarche. Leaflet media is most effective on anxiety levels and readiness to face menarche. Thus video education media, leaflets and lectures have an effect on anxiety levels and readiness to face menarche
Keywords: Adolescent Girls, Anxiety, Education, Leaflet, Menarche